PEMANFAATAN DATA PENGINDERAAN JAUH DAN SIG UNTUK KAJIAN KONVERSI LAHAN PERTANIAN MENJADI NONPERTANIAN DI SEBAGIAN KABUPATEN BANTUL - , BARID SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Changes in land use particularly agriculture land into non-agricultural conversion proceed quickly, it causes narrowing of productive agricultural land while the land up getting widespread. Reduction in agricultural land can indirectly affect agricultural output is not the maximum , but it woke up the area that is growing rapidly exceed the existing provisions in the draft layout, so that need for monitoring of land conversion. Effort to monitor and analyze the factors that affect the conversion of agricultural land into non-agricultural in 2001-2007 can be either terrestrial , but this method requires the cost, time and cost relatively much. To be more effective and efficient then one solution is to use remote sensing techniques. The purpose of this study is to utilize remote sensing data and Geographic Information Systems ( GIS ) to determine the conversion of agricultural land into non-agricultural part of Bantul, mapping of land conversion based on the interpretation of multitemporal remote sensing data. The method used in this study is the integration of remote sensing , GIS , secondary data, and field checks . Method of remote sensing and aerial photo interpretation techniques Ikonos imagery , overlay , multitemporal analysis and qualitative analysis to determine and describe the relationship of variable influence, in this study used a black and white panchromatic aerial photo scale of 1 : 20.000 years of shooting 2001 and 2007 recording of Ikonos imagery. Classification used is the classification by Sutanto (1981 ) with modifications. The results of the study obtained information that the accuracy of test results from the utilization of remote sensing data interpretation accuracy value of 83,20 % . Land conversion that occurred during the years 2001-2013 in most districts of Bantul cause agricultural changes into residential land area of 792,76 ha. Through qualitative analysis can be known and described that the factors that influence land conversion include: an increase in population, the availability of accessibility of a road network, workers in the agricultural sector, and the presence of natural events such as earthquake . Meanwhile many areas experiencing conversion of agricultural land into non-agricultural is Bantul district, Bantul, distribution patterns form si a diffuse pattern of land conversion.